1998
DOI: 10.3168/jds.s0022-0302(98)75668-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ruminal Bypass Lysine and Methionine on Milk Yield and Composition of Lactating Cows

Abstract: Fifty-six multiparous Holstein cows were assigned at 3 wk prepartum to rations based on grass silage with 1) corn distillers grains to provide 86 and 90% of estimated required metabolizable Lys and Met, respectively; 2) a blend of blood meal, fish meal, and meat and bone meal as amino acid (AA) sources to provide 112 and 103% of required metabolizable Lys and Met, respectively; 3) ruminally protected Lys and Met added as a top-dressing to ration 1 to provide 27 g/d of Lys and 8 g/d of Met as available AA at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
63
3
11

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 33 publications
14
63
3
11
Order By: Relevance
“…This effect is a common feature of experiments involving protected forms of methionine (Overton et al, 1996(Overton et al, , 1998Rulquin and Delaby, 1997;Overton et al, 1998;Xu et al, 1998). Moreover, elevated levels of methionine metabolites, such as taurine, were consistent with the results of similar experiments using methionine (Overton et al, 1996;Pisulewski et al, 1996;Rulquin and Delaby, 1997).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This effect is a common feature of experiments involving protected forms of methionine (Overton et al, 1996(Overton et al, , 1998Rulquin and Delaby, 1997;Overton et al, 1998;Xu et al, 1998). Moreover, elevated levels of methionine metabolites, such as taurine, were consistent with the results of similar experiments using methionine (Overton et al, 1996;Pisulewski et al, 1996;Rulquin and Delaby, 1997).…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, postruminal methionine did not affect DMI or milk yield of cows fed with maize silage (Pisulewski i in., 1996;Rulquin and Delaby, 1997) or lucerne-maize silage-based diets (Overton et al, 1996(Overton et al, , 1998. However, in some conditions, supplementing grass silage-based diets with protected (lysine and methionine) amino acids increases DMI (Xu et al, 1998). Since milk yield of dairy cows may be increased by supplemental amino acids in the early stages of lactation, and not in mid-or late lactation (Rulquin, 1992) we did not expect marked changes of these measurement in our studies (Table 3).…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…Korhonen et al (2000) mentioned His as the first limiting AA in diets based on grass silage and, according to Vanhatalo et al (1999) His has been identified as a potentially limiting AA for milk production. Other authors mentioned as limiting the combinations of Met with Leu (Krober et al, 2001) and/or with His and Arg (Xu et al, 1998). The problem of limiting AA has been relatively well investigated in studies on the supply of Met and Lys but not enough data are available for other AA or their combinations.…”
Section: Introductionmentioning
confidence: 99%